Patient satisfaction with nursing care quality in affiliated hospitals of an educational institution - Claro, Queenne Kimverlee C. (Technium Social Sciences Journal, 2022)
The purpose of this study is to assess the patient satisfaction towards nursing care in a private and public hospitals affiliated to an educational institution in Santiago City. A descriptive cross-sectional survey design was used in the study. The analytical sample was composed of 210 participants from the two hospitals. Data were collected using the Patient Satisfaction with Nursing Care Quality Questionaire with a total of 19 items and designed to record the demographic information of the participants. The results of the study on the level of satisfaction with nursing care quality of the hospitals indicated very satisfied (M=3.53, SD=0.85). There were significant differences on age, marital status and educational attainment but no significant difference on gender. Also, There were no significant difference on patients satisfaction with nursing care quality across the combined same wards of the private and public hospitals. But then, there was a significant difference on patients satisafaction with nursing care quality on private from public hospital wards.